2018
DOI: 10.1007/s00253-018-9296-7
|View full text |Cite
|
Sign up to set email alerts
|

Stable transformation of Spirulina (Arthrospira) platensis: a promising microalga for production of edible vaccines

Abstract: The planktonic blue-green microalga Spirulina (Arthrospira) platensis possesses important features (e.g., high protein and vital lipids contents as well as essential vitamins) and can be consumed by humans and animals. Accordingly, this microalga gained growing attention as a new platform for producing edible-based pharmaceutical proteins. However, there are limited successful strategies for the transformation of S. platensis, in part because of an efficient expression of strong endonucleases in its cytoplasm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…To produce the designed recombinant protein vaccine in a lab setting, a suitable expression host such as microalgae can be used to express the recombinant vaccine with the optimal post-translational modi cations 56,57 . In the case of SAMV construct, although both the non-viral delivery systems (e.g., lipid nanoparticles 58 , polymeric nanoparticles 59 , and cell-penetrating peptides 60 ), and in vivo transfection systems (e.g., injection, electroporation, and gene gun) can improve the stability and cellular uptake e cacy, however, the naked SAM vaccine can be taken up as well by signi cantly antigen-presenting cells without any additional required formulation 61 .…”
Section: Discussionmentioning
confidence: 99%
“…To produce the designed recombinant protein vaccine in a lab setting, a suitable expression host such as microalgae can be used to express the recombinant vaccine with the optimal post-translational modi cations 56,57 . In the case of SAMV construct, although both the non-viral delivery systems (e.g., lipid nanoparticles 58 , polymeric nanoparticles 59 , and cell-penetrating peptides 60 ), and in vivo transfection systems (e.g., injection, electroporation, and gene gun) can improve the stability and cellular uptake e cacy, however, the naked SAM vaccine can be taken up as well by signi cantly antigen-presenting cells without any additional required formulation 61 .…”
Section: Discussionmentioning
confidence: 99%
“…39 It should be noted that probiotics similar to many of microalgae (e.g., Dunaliella and Spirulina species) may be generally regarded as safe for use in animal and human systems. 29,40,41 Taken all, these organisms could be assigned as an important vehicle for oral delivery of different biologics such as edible vaccines. 42…”
Section: Discussionmentioning
confidence: 99%
“…20 The gene silencing is deemed to happen at both transcriptional and translational levels due to the functional presence of nuclease and proteases in the microalgae cytosol. 4 In addition, the insertion of the genes of interest (GOIs) into the nuclear genome might occur randomly, causing the truncate of the important host genes or even cell death. 10 Recent researches identified codon optimization using native and chimeric strong promoters and showed that the untranslated regions (UTRs) might be involved in the gene expression of microalgae.…”
Section: Agrobacterium-2a-based Plasmid Constructionmentioning
confidence: 99%
“…As a result, they can be exploited for different biomedical applications even the treatment of various diseases such as cancer. 4 Moreover, the eyespot and channelrhodopsins in the microalgae are located in the center of optogenetic and neuroscience for illuminating the fundamentals of eyes and brain functions. [5][6][7] Although the genetic manipulation of microalgae is lower than that of the other expression hosts, their key characteristics make them an interesting expression platform for the production of recombinant proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation